Next-generation Sequencing and Karyotype Analysis for the Diagnosis of Robertsonian Translocation Type Trisomy 13: A Case Report - Jing SHA; Fumin LIU; Bei ZHANG; Yang HUANG; Qinglin ZHANG; Gao JUAN; Jingfang ZHAI (Tehran University of Medical Sciences, 2017)
Trisomy 13 (Patau syndrome) is the third most common autosomal trisomy with a prevalence between 1 in 10,000 - 20,000 live births. Robertsonian translocations represent the largest number of chromosomal aberrations in human population with an incidence of 1.23 in 1000 live birth and translocation 13;14 is one of the most frequent Robertsonian translocations (approximately 75%). We sampled umbilical vein blood from a 27-yr-old woman whose ultrasonography findings revealed congenital heart defects, single ventricle, polycystic kidney, median cleft lip and palate and holoprosencephaly at gestational age of 23+6 weeks for karyotype and sequencing during intra-amniotic cavity injection of acrinol for labor induction. Next-generation sequencing indicated 47,XN,+13 and karyotype was identified as 46,XN,+13,rob (13;14). An unexpected problem becomes more and more obvious in human cytogenetics - it seems to become difficult to decide how and when to use the "molecular cytogenetics" or "traditional karyotype analysis". Molecular cytogenetics, such as next-generation sequencing and array-based comparative genomic hybridization (array-CGH), can detect microdeletions and micro-duplications, but it cannot detect balanced translocations. For this case, we cannot find balanced translocations by Molecular cytogenetics. The purpose of this case is that molecular cytogenetics cannot replace the traditional karyotype analysis, but can serve as a useful complement for G-banding to be used in the clinical cytogenetic diagnosis.